Peran Bimbingan dan Konseling Islam dalam penguatan dakwah berbasis nilai qur'ani - Indah Zakiyyatul Miskiyyah (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2025)
Islamic Guidance and Counseling play a vital role in supporting holistic individual development, encompassing spiritual, emotional, and social dimensions. Within the context of Qur’an-based da’wah (Islamic preaching), Islamic Guidance and Counseling serve as an approach that integrates Islamic values contained in the Qur’an into the process of community development. This study aims to interpret and analyze the role of Islamic Guidance and Counseling in strengthening da’wah grounded in Qur’anic values, emphasizing the integration of psychological, spiritual, and social aspects in Islamic counseling practices as a means of conducting da’wah that is relevant, factual, and contextual in modern society. The method used in this study is a qualitative approach with descriptive analysis. Data were obtained through literature review, including relevant studies on Islamic guidance and counseling and da’wah. Data analysis involved content analysis of academic articles, previous research reports, classical Islamic references, and academic books. The findings indicate that the counselor (da’i), the counselee (mad’u), and the problem itself each play a significant role in strengthening Qur’an based da’wah. In conclusion, Islamic Guidance and Counseling function not only as a means of providing psychological and spiritual assistance but also as a medium for conveying da’wah messages through a professional approach grounded in the Qur’an and Hadith. It can serve as an effective means of nurturing the ummah, fostering religious awareness, independence, and spiritual balance within the life of modern society.